2008
DOI: 10.1186/1471-2458-8-106
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of four scoring methods based on the parent-rated Strengths and Difficulties Questionnaire as used in the Dutch preventive child health care system

Abstract: BackgroundValidated questionnaires can support the identification of psychosocial problems by the Preventive Child Health Care (PCH) system. This study assesses the validity and added value of four scoring methods used with the Strengths and Difficulties Questionnaire (SDQ) for the identification of psychosocial problems among children aged 7–12 by the PCH.MethodsWe included 711 (of 814) children (response: 87%) aged 7–12 undergoing routine health assessments in nine PCH services across the Netherlands. Child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 20 publications
5
60
0
3
Order By: Relevance
“…Moreover, previous research identified a lower 10% cutoff point for Dutch children [11,43]. Possibly, there is a comparable bias for Flemish children.…”
Section: Study Limitationsmentioning
confidence: 88%
“…Moreover, previous research identified a lower 10% cutoff point for Dutch children [11,43]. Possibly, there is a comparable bias for Flemish children.…”
Section: Study Limitationsmentioning
confidence: 88%
“…Previous research has shown that the use of validated questionnaires, training of PCH professionals in a structured method for identifying psychosocial problems, and providing more time for the assessment may improve the accuracy of this early identification. 39,40 This study may add to the improvement of the quality of early identification in routine practice by indicating the predictors for behavioral problems that should be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Important to appreciate is that measurement across the two studies were not identical, even if highly similar, and that policies and practices of schools in the two countries cannot be presumed to be the same. (Crone, Vogels, Hoekstra, Treffers, & Reijneveld, 2008), which was used for screening. Completed SDQs were returned by 3,358 of 3,456, families (97.2%) at the Well Child Clinics (when the child attended a routine health check for 4-year-olds).…”
Section: Gene-؋-environment Interactionmentioning
confidence: 99%